2021
DOI: 10.3389/fneur.2021.666427
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Direct Visualization of the Nervus Intermedius During the Microvascular Decompression Procedure: Should We Take It Seriously?

Abstract: Background: Nervus intermedius neuralgia (NIN), known as geniculate neuralgia (GN), is an uncommon cranial nerve disease caused by an offending vessel compressing the nervus intermedius (NI). Microvascular decompression (MVD) has now become a valued treatment approach for NIN because it can resolve neurovascular conflict (NVC) at the root entry zone of the NI. In the era of continuously optimizing and improving the surgical technique of MVD, further minimization of all possible postoperative complications is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 28 publications
0
4
0
8
Order By: Relevance
“…It has been reported that complications occur more frequently in cases of MVD for INN in which the intermediate nerve is visualized than in those in which it is not. Furthermore, the authors noted that there is no need to confirm intermediate nerve intraoperatively forcibly [7]. In this case, the intermediate nerve was easily visible because the AICA loop from the dorsal side compressed it.…”
Section: Decompressed Both Have Been Shown To Have Good Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…It has been reported that complications occur more frequently in cases of MVD for INN in which the intermediate nerve is visualized than in those in which it is not. Furthermore, the authors noted that there is no need to confirm intermediate nerve intraoperatively forcibly [7]. In this case, the intermediate nerve was easily visible because the AICA loop from the dorsal side compressed it.…”
Section: Decompressed Both Have Been Shown To Have Good Resultsmentioning
confidence: 81%
“…The intermediate nerve is reported to be challenging in the operative field because it is located dorsal to the vestibulocochlear nerve [7]. There are concerns that the vestibulocochlear nerve may be strained because of the visibility of the intermediate nerve, resulting in hearing loss as a complication [7].…”
Section: Decompressed Both Have Been Shown To Have Good Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ввиду редкости заболевания точная причина НПН остается неизвестной [4]. Существует предположение об инфекционной природе заболевания (Нerpes zoster, в частности синдром Рамсея Ханта), но наиболее вероятная причина -компрессия промежуточного нерва (ПН) вследствие нейроваскулярного конфликта (НВК) [5,6].…”
Section: O N T a C T Sunclassified
“…When treating patients with severe brain contusion, it is crucial to monitor internal pressure (ICP), especially when their Glasgow Coma Scale (GCS) is lower than 8. Microvascular decompression is a recognized treatment option for releasing ICP ( 11 ). In addition to traditional treatment methods, cutting-edge treatment technologies are also being developed and tested.…”
Section: Introductionmentioning
confidence: 99%